THE EFFECT OF PROMOTION, PRICE, AND CUSTOMER RATING ONLINE ON THE BUYING DECISION OF TOKOPEDIA E-COMMERCE: A CASE STUDY IN PADANG - Afrinaldi, Muhamad; Wiratha, Andre (Universitas Terbuka, 2024)
This study aims to analyze the impact of promotions, pricing, and online customer ratings on purchasing decisions in the Tokopedia e-commerce platform in Padang City. Data were collected through a questionnaire that was tested for validity and reliability. Regression analysis results indicate that promotions and online customer ratings have a significant positive influence on purchasing decisions, while pricing does not have a substantial impact. These findings provide insights for business practitioners in designing effective marketing strategies in the digital era. It is recommended that sellers continuously optimize promotional strategies, set competitive prices, and manage customer reviews effectively to enhance purchasing decisions. Promotional activities are considered highly important in boosting purchasing decisions, whereas high prices may reduce consumer interest.